PENGUATAN PERAN KELUARGA DALAM PENCEGAHAN STUNTING PADA ANAK MELALUI PENDEKATAN PROMOTIF DAN PREVENTIF - Wa Ode Sitti Zubaydah; Parawansah Parawansah; Selvi Selvi; Waode Shima Indisia; Molifa Dalis; Anisa Fauzia Asri; Fatimardiyach Rahmi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stunting is a chronic nutritional issue resulting from prolonged malnutrition during a child's growth and development, leading to impaired physical growth and brain development. The initiative employed an outreach approach conducted as part of a community service program. The objective was to provide the community with direct information regarding stunting, health education, and the family's role in early prevention. The activity took place at the Benu-Benua Community Health Center in Puunggaloba Village, Kendari City, Southeast Sulawesi. The target audience consisted of local mothers with children under the age of five. The program involved presentations covering the definition of stunting, its causes, and prevention strategies. Results indicated active participant engagement and increased awareness regarding the importance of proper child nutrition. However, the findings also revealed that the community's level of knowledge concerning stunting remains low. Therefore, sustained health and nutrition education programs are necessary.